Word-level prosodic measures and the differential diagnosis of apraxia of speech. (4th May 2019) - Haley, Katarina L.; Jacks, Adam
ABSTRACT: Impaired production of prosody is considered a primary diagnostic criterion for apraxia of speech. In this study, we examined diagnostic relevance for five word-level prosody measures. Seven speakers with AOS, nine with aphasia and no AOS, and 19 age-matched neurotypical controls produced nine words consisting of three or four syllables. Lexical stress indices were computed based on relative values for duration, fundamental frequency, and intensity across pairs of unstressed-stressed syllables with varying intrinsic vowel duration contrast patterns. A simple average syllable duration measure was also obtained. AOS speakers differed from the other two groups on three metrics that were solely or primarily derived from duration measures. The degree of diagnostic overlap was smallest for the syllable duration metric, which also showed the strongest inter-observer reliability and most complete overlap between neurotypical speakers and speakers with aphasia and no AOS. Vowel intrinsic durational properties affected lexical stress metrics significantly, indicating a need to select word targets purposefully. Based on these results, it appears that the average syllable duration metric is a more stable and informative alternative for differential diagnostic purposes. The results will, however, need to be replicated in a larger sample.